2017
DOI: 10.1161/circresaha.116.309955
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Risk Markers and Risk Assessments for Cardiovascular Disease

Abstract: Abstract:The use of risk markers has transformed cardiovascular medicine, exemplified by the routine assessment of troponin, for both diagnosis and assessment of prognosis in patients with chest pain. Clinical risk factors form the basis for risk assessment of cardiovascular disease and the addition of biochemical, cellular, and imaging parameters offers further refinement. Identifying novel risk factors may allow greater risk stratification and a steady, but gradual progression toward precision medicine. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 189 publications
(200 reference statements)
2
85
1
5
Order By: Relevance
“…The role of HDL‐c, however, has been brought into question by negative findings from clinical drug trials and negative Mendelian randomization studies 32. In our study binge drinking was associated with higher HDL‐c levels, and in all groups HDL‐c levels were greater than 50 mg/dL.…”
Section: Discussioncontrasting
confidence: 43%
“…The role of HDL‐c, however, has been brought into question by negative findings from clinical drug trials and negative Mendelian randomization studies 32. In our study binge drinking was associated with higher HDL‐c levels, and in all groups HDL‐c levels were greater than 50 mg/dL.…”
Section: Discussioncontrasting
confidence: 43%
“…; Ruparelia et al. ; Thomas and Lip ). Numerous clinical and experimental studies have shown that infection with various bacterial pathogens including Porphyromonas gingivalis may serve as an additional risk factor in the development and progression of atherosclerosis (Tonetti ; Kebschull et al.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this advancement in immunophenotyping is CyTOF, a leukocyte phenotyping assay which can be performed on patient‐derived peripheral blood mononuclear cells stained with isotopically pure lanthanide metal‐conjugated antibodies (Table ). This allows up to 40 markers to be examined on 1 run, and subsequently analyzed by mass spectrometry TOF, providing numeration and characterization of circulating leukocyte cell subsets . This generates a leukocyte “signature” in which the number and functional status of each subset indicates past and present inflammation and immune activity.…”
Section: Candidate Approaches—the “Inflammasome” Dysregulated Redox mentioning
confidence: 99%
“…39 C, It is the structure and function of HDL rather than its plasma concentration that is more closely associated with cardiovascular risk, likely through its impact on cholesterol efflux capacity and RCT 7 new insights may be gained by rapid technical and bioinformatics advances in immunophenotyping. An example of this advancement in immunophenotyping is CyTOF, a leukocyte phenotyping assay which can be performed on patient-derived peripheral blood mononuclear cells stained with isotopically pure lanthanide metal-conjugated antibodies 29,30 (Table 1). This allows up to 40 markers to be examined on 1 run, and subsequently analyzed by mass spectrometry TOF, providing numeration and characterization of circulating leukocyte cell subsets.…”
Section: And Idate Approache S-the " Infl Amma Some " Dys Reg Ulmentioning
confidence: 99%